SOUNDS AND PRONUNCIATION (Children's First Language Acquisition Model in the Pragmatic Process) - Memmy Dwi Jayanti (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract: The aim of the study was to determine the stages of the linguistic first language acquisition process which emphasized the aspects of sound and pronunciation in children aged two to four years. Research focuses on phonological analysis of sound and pronunciation in a pragmatic perspective. This type of qualitative research uses a cross sectional approach, namely data collection from the age of two to four years at the same time in order to obtain complete and fast data so that it can describe each individual in the process of acquiring his language. The focus of research is all sounds or sounds that are spoken or produced by the child in a pragmatic view, namely when communicating. Sub focus in research is the sound and pronunciation of children according to the theory of Susan M. Gass and Larry Se, at the initial stage the pronunciation of children is not the same as the pronunciation of adults. Some sounds can be distinguished at first such as: the difference between consonants in [ta] and [da]. Even when children start using words that more or less resemble adult words, at least in a sense, there are different pronunciations, namely deletion of syllables (em..bek→goat), elimination of sound (japah→jerapah→giraffe), and simplification process words (fis→fish). The results showed that there was a relationship between the ability of sound produced by children and pragmatic rules according to their age. In the acquisition of languages and stages of linguistic processes with almost the same age there are also differences between children with each other.